2015
DOI: 10.1096/fj.14-267187
|View full text |Cite
|
Sign up to set email alerts
|

Activation of autophagy in human skeletal muscle is dependent on exercise intensity and AMPK activation

Abstract: In humans, nutrient deprivation and extreme endurance exercise both activate autophagy. We hypothesized that cumulating fasting and cycling exercise would potentiate activation of autophagy in skeletal muscle. Well-trained athletes were divided into control (n = 8), low-intensity (LI, n = 8), and high-intensity (HI, n = 7) exercise groups and submitted to fed and fasting sessions. Muscle biopsy samples were obtained from the vastus lateralis before, at the end, and 1 h after a 2 h LI or HI bout of exercise. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
142
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 45 publications
18
142
2
Order By: Relevance
“…Our data show that aerobic exercise induces a reduction in p62/SQSTM1, suggesting an increase in the expression of autophagy regulatory proteins after the training program. These results are in line with previous studies which showed an increase in LC3II and a decrease in p62/SQSTM1 expression after exercise in different rodent (He et al 2012;Lira et al 2013;Bayod et al 2014) and human models (Schwalm et al 2015), hence supporting the notion that high-intensity exercise induces an increased autophagy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data show that aerobic exercise induces a reduction in p62/SQSTM1, suggesting an increase in the expression of autophagy regulatory proteins after the training program. These results are in line with previous studies which showed an increase in LC3II and a decrease in p62/SQSTM1 expression after exercise in different rodent (He et al 2012;Lira et al 2013;Bayod et al 2014) and human models (Schwalm et al 2015), hence supporting the notion that high-intensity exercise induces an increased autophagy.…”
Section: Discussionsupporting
confidence: 92%
“…Among interventions aimed to prevent or reverse these undesirable effects, the role of exercise is growing (Vainshtein et al 2014). Indeed, both acute and chronic endurance exercise seem to induce adaptations in the autophagy pathway Jamart et al 2012;Schwalm et al 2015;Weng et al 2013). However, it should be noted that most of the available data related to the effects of exercise on autophagy proteins in different tissues have been obtained from rodent studies, where long training periods induce a significant increase in the protein expression of beclin-1 and LC3I/II associated to a lowered expression of p62/SQSTM1 in muscles (He et al 2012;Kim et al 2013;Lira et al 2013; (Bayod et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in well-trained human skeletal muscle there is no synergistic effect of prior fasting on autophagy signalling compared with commencing the exercise bout in the fed state, with exercise intensity mitigating the largest autophagic response to contraction (Schwalm et al, 2015). Regardless, specific autophagosomal targeting of mitochondria for degradation, termed mitophagy, constitutes a form of mitochondrial remodelling provoked by endurance exercise.…”
Section: Reduced Energy Availabilitymentioning
confidence: 99%